2019
DOI: 10.1371/journal.pone.0225513
|View full text |Cite|
|
Sign up to set email alerts
|

Seasonal alternation of the ontogenetic development of the moon jellyfish Aurelia coerulea in Maizuru Bay, Japan

Abstract: Outbreaks of moon jellyfish Aurelia spp. are frequently reported from many parts of the world’s coastal areas. Aurelia spp. canonically show a metagenetic life cycle in which planulae transform into sessile polyps, which can drastically increase in number through asexual reproduction. Therefore, their asexual reproduction has been recognized as one of the major causes of the outbreaks. Aurelia spp. also show direct development that lacks asexual reproduction during the polyp stage, which prevents us from under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 78 publications
2
25
0
Order By: Relevance
“…Precipitation is rather high from summer to winter that is the rainy season in this area. Sea-surface temperature ranged from 5.2 to 31.8°C, sea bottom temperature from 8.5 to 29.6°C, which were measured near the surface and at the depth of 10 m underwater during the diving, respectively [86].…”
Section: Methodsmentioning
confidence: 99%
“…Precipitation is rather high from summer to winter that is the rainy season in this area. Sea-surface temperature ranged from 5.2 to 31.8°C, sea bottom temperature from 8.5 to 29.6°C, which were measured near the surface and at the depth of 10 m underwater during the diving, respectively [86].…”
Section: Methodsmentioning
confidence: 99%
“…The size of fully-developed A. hardenbergi polyps was about 0.4 mm, which is smaller compared to other scyphistomae. Therefore, A. hardenbergi polyps made ephyrae as large as possible by mono-disc strobilation and tiny residuum tissue remained, like the direct development of planula (planula strobilation) in Aurelia coerulea [47][48][49][50]. However, the residuum could not develop into the polyp, and it disappeared.…”
Section: Strobilation Stagementioning
confidence: 99%
“…However, it was reported that A. aurita in Germany, and A. aurita [later changed to A. coerulea (Scorrano et al 2016)] in Japan (Fig. 1) have shown another variation in their life cycle, where the planula ostensibly metamorphoses directly into an ephyra, omitting the polyp stage after settling on substrate (Haeckel 1881;Hirai 1958;Kakinuma 1975;Miyake et al 2019;Suzuki et al 2019;Yasuda 1975Yasuda , 1979Lucas 2001). This was called 'Ephyra pedunculata ' by Haeckel (1881) and Hirai (1958) and is currently referred to these days as 'direct development' (Berrill 1949;Hirai 1958;Kakinuma 1975;Yasuda 1975Yasuda , 1979Arai 1997;Lucas 2001).…”
Section: Introductionmentioning
confidence: 99%
“…2. The mature oocytes of medusae in the areas where the planula-strobilation type is distributed are large (Kon and Honma 1972;Yasuda 1988;Suzuki et al 2019). 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation